(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In a country that aspires for sustainable and equitable growth, financial inclusion is nothingless than a prerequisite condition. Financial Inclusion is recognized as an important tool when it comesto policy framing for the underprivileged and vulnerable section of society.It is about delivering bankingand financial services at an affordable cost to the underprivileged sections of disadvantaged people.This paper-based on thorough review of the existing literature is an attempt to study the current status offinancial inclusion in Rajasthan. Hostile climate conditions, arid terrain, weak infrastructure, andfrequent droughts are a few of the factors that have impeded the state’s efforts toward its developmentwhich further entails financial inclusion as an important tool in ensuring the state overcomes a few of itschallenges.